2013
DOI: 10.1002/bjs.9112
|View full text |Cite
|
Sign up to set email alerts
|

Optimal time interval between neoadjuvant chemoradiotherapy and surgery for rectal cancer

Abstract: Delaying surgery until the 15th or 16th week after the start of CRT (10-11 weeks from the end of CRT) seemed to result in the highest chance of a pCR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
163
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 240 publications
(172 citation statements)
references
References 26 publications
8
163
0
1
Order By: Relevance
“…Notably, with a median 45-day interval between preoperative ccrt and surgery, our findings indicate that prolongation of surgery beyond 6 weeks after ccrt had no significant effect on survival or tumour response. Similarly, in a study conducted with 1593 patients attending 92 Dutch hospitals who underwent preoperative ccrt, the highest chance of pathologic complete response was noted when the interval between ccrt and surgery was about 11 weeks, with no apparent further increase being noted beyond that time 14 . Prolongation of the interval to 6-8 weeks or more from 4-6 weeks to improve rates of local control or survival has been considered not to be reasonable in tumours considered upfront to be resectable 15 .…”
Section: Discussionmentioning
confidence: 90%
“…Notably, with a median 45-day interval between preoperative ccrt and surgery, our findings indicate that prolongation of surgery beyond 6 weeks after ccrt had no significant effect on survival or tumour response. Similarly, in a study conducted with 1593 patients attending 92 Dutch hospitals who underwent preoperative ccrt, the highest chance of pathologic complete response was noted when the interval between ccrt and surgery was about 11 weeks, with no apparent further increase being noted beyond that time 14 . Prolongation of the interval to 6-8 weeks or more from 4-6 weeks to improve rates of local control or survival has been considered not to be reasonable in tumours considered upfront to be resectable 15 .…”
Section: Discussionmentioning
confidence: 90%
“…23,24 In the Dutch Surgical Colorectal audit evaluable patients who underwent preoperative CRT for rectal cancer between 2009 and 2011 were evaluated to determine the influence of the interval between radiotherapy and surgery, which was calculated from the start of radiotherapy. 5 In this study an interval of 15-16 weeks after the start of CRT resulted in the highest pCR rate (18·0 per cent; P = 0·013), with an independent association (hazard ratio 1·63, 95 per cent confidence interval 1·20 to 2·23). In a recent Polish study, 154 patients were randomized to SCPRT with surgery either 7-10 days or 4-5 weeks after the end of RT.…”
Section: For Debatementioning
confidence: 50%
“…4 However, further extensions of this interval do not appear to benefit the patient. 5,6 Patients with rectal cancer, who achieve a pCR or near pCR, fare consistently better than the patients who fail to do so. 7 In contrast, patients with no evidence of response fare badly.…”
Section: For Debatementioning
confidence: 99%
“…Several studies have shown a higher degree of downsizing and downstaging 10e12 weeks after completion of CRT before surgery. 18,19 At the time of this study the general policy was to perform surgery after eight weeks. CK 20 is a well known stable biomarker for colorectal cancer.…”
Section: Discussionmentioning
confidence: 99%